The emerging role of cardiopulmonary exercise testing and cardiac rehabilitation in dilated cardiomyopathy: A mini review - Saba Murad,; Muhammad Ehab Azim,; Furqan Ahmed Siddiqi,; Farooq Azam Rathore, (Journal of the Pakistan Medical Association, 2024)
Cardiovascular mortality is a major health burden worldwide and the number of patients with cardiac diseases is increasing. Dilated cardiomyopathy (DCM) is the most frequent cause for patient visits in cardiac care units and emergency departments. It is commonly misdiagnosed as ischaemic cardiac disease. Middle- and low-income countries rely on pharmacological management as the only treatment option. Most of the patients cannot afford heart transplants or advanced treatment strategies. Most health professionals also do not prescribe cardiac rehabilitation for DCM patients in their routine clinical practice. There is evidence that supervised cardiac rehabilitation is safe and beneficial for DCM patients. In addition to medications, cardiopulmonary exercise testing (CPET) and supervised cardiac rehabilitation, can provide more benefits to the affected population of cardiomyopathies. CPET and cardiac rehabilitation are still novel concepts in countries like Pakistan. The present review aims to provide clinicians with an overview of an evidence-based and innovative perspective. This perspective emphasizes the utilization of the additional benefits of cardiac rehabilitation in the holistic management of DCM patients and the prevention of chronic heart failure. Keywords: Cardiac Rehabilitation, Cardiopulmonary exercise testing, CPET, DCM, Exercise, Idiopathic Dilated Cardiomyopathy, Risk stratification.